“Yeah, I Know You Always Stay”: Menjelajahi Dunia Virtual ARMY pada Fanbase @bitiesfess Selama Hiatus Grup - Rahman, Meilya Syifa Aghniya; Achmad, Zainal Abidin (JURNAL SOSIAL HUMANIORA (JSH), 2024)
Cultural researchers have long been concerned about the development of K-Pop fan activities. ARMY fandom stands out as a unique research subject because this community has its style of expressing feelings and admiration for BTS. Within a virtual community of fans (fanbase), ARMY fandom gathers and interacts actively. ARMY Indonesia actively builds fan closeness, exemplified by the @bitiesfess fanbase. Even when the group undergoes military service (hiatus), ARMY Indonesia actively communicates and supports BTS. Researchers analyzed fan interactions using a virtual ethnographic approach. The research results reveal four key areas of fandom interaction in the @bitiesfess fanbase: 1) The communication area actively segments into four forms: real-time updates, fan jokes, nostalgia, and exposure. 2) The fanbase's creativity field actively comprises various fan edits and memes. 3) The field of knowledge during the hiatus period actively dominates with activity schedules, member updates, education, advice, and fun facts. 4) The organization and civil power field actively invite followers to support movements, e.g., streaming, philanthropy, reporting and blocking, and advocacy campaigns.